2010
DOI: 10.1007/s00436-010-2102-9
|View full text |Cite
|
Sign up to set email alerts
|

Protein change of intestinal epithelial cells induced in vitro by Trichinella spiralis infective larvae

Abstract: The aim of this study was to observe the protein changes of intestinal epithelial cells induced in vitro by Trichinella spiralis infective larvae and their excretory-secretory (ES) or surface antigens and identity the proteins related with invasion. HCT-8 cells were incubated for 2 h in the culture medium contained ES or surface antigens of infective larvae, and observed by Immunofluorescent test (IFT). The infective larvae were inoculated into culture of HCT-8 cells to incubate for 18 h, and the lysates of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Protein samples (20 g) were separated by SDS-PAGE on 5% stacking gels and 12% resolving gels (83 × 73 × 1.0 mm) in a minivertical electrophoresis system (Bio-Rad Laboratories, USA) (Wang et al, 2011). After electrophoresis, the gel was stained with 0.25% Coomassie brilliant blue (CBB) R-250 (Sigma, USA) for 4 h, and then bleached with the eluate.…”
Section: Sds-pagementioning
confidence: 99%
“…Protein samples (20 g) were separated by SDS-PAGE on 5% stacking gels and 12% resolving gels (83 × 73 × 1.0 mm) in a minivertical electrophoresis system (Bio-Rad Laboratories, USA) (Wang et al, 2011). After electrophoresis, the gel was stained with 0.25% Coomassie brilliant blue (CBB) R-250 (Sigma, USA) for 4 h, and then bleached with the eluate.…”
Section: Sds-pagementioning
confidence: 99%
“…32,33,[38][39][40][41] Studies in which helminth E/S products are added directly to epithelial monolayers and permeability subsequently assessed are scarce. The E/S products from the nematodes Haemonchus contortus and Teladorsagia circumcincta when applied to the apical surface of monolayers of the human colon-derived Caco2 epithelial cell line lowered the TER by »20% 2 hours post-treatment.…”
Section: Increased Epithelial Permeability Triggered By Infection Witmentioning
confidence: 99%
“…These figures are representative of three independent experiments as growth factors, proteases and cytokine (Guttridge et al 1997;Olwin and Rapraeger 1992;Rao and Kohtz 1995;Zorzano et al 2003). A previous study suggested that ML-ESP of T. spiralis may be combined to the surface of intestinal epithelial cells and induce the specific mediators or signal transduction protein, which could facilitate larvae invasion (Wang et al 2011). From the results presented here, we speculate that factors within the ML-ESP reversibly bound to specific receptors at the surface of the myoblast to modulate cellular proliferation and differentiation via the activation of specific intracellular signalling cascades.…”
Section: Discussionmentioning
confidence: 98%